Racial Differences in Associations of Cognitive Health Status With Happiness, Helplessness, and Hopelessness Among Older Adults: An Exploratory Study - Umucu, Emre; Lee, Beatrice; Wyman, Mary; Gooding, Diane Carol; Van Hulle, Carol Ann; Johnson, Adrienne; Ferrer Simo, Carola A.; Carter, Fabu; Salazar, Hector; James, Taryn T.; Bouges, Shenikqua; Lambrou, Nicholas H.; et al. (Frontiers in Aging Neuroscience, 2022)
Background: The relationship between healthy and positive aging and dementia and cognitive impairment has received limited attention in the field of aging. Affect impacts cognitive changes and processes, and cognitive impairment is associated with affective comorbidities. The purpose of the study was to examine (a) whether happiness, helplessness, and hopelessness are linked to cognitive health status, and (b) whether these associations differ by race. Methods: Participants were enrollees in the Wisconsin Alzheimer’s Disease Research Center’s Clinical Core (ADRC). Average age at baseline was 60.85 (SD = 8.65), 73.70 (SD = 8.02), and 73.80 (SD = 9.59) years for cognitively normal individuals, individuals with MCI, and individuals with dementia, respectively. Results: In the full sample, chi-square test results revealed associations between Cognitive Health Status (CHS and (a) happiness), χ2 (2) = 6.06, p < .05, (b) helplessness, χ2 (2) = 6.44, p < .05, and (c) hopelessness, χ2 (2) = 14.11, p < .01. Conclusions: This study provides support for the association of both positive and negative affect with cognitive health status in middle- to older-aged adults.